Nullification of Arbitral Award Under UAE Law Dissertation - ELSANOSI, AHMED (2023)
The UAE Arbitration community has welcomed the new UAE Arbitration Law enacted on 2018 which adds popularity to UAE as an internationally recognised environment for Arbitration as parties normally elect to opt out from Courts and choose Arbitration to resolve their disputes mainly due to is fast decisions and procedures’ flexibility compared to Court litigations, however for the Arbitral Awards to be executable, it must be enforced by recourse to the Courts who has the power to affirm, annul or grant leave for correction of Arbitral Awards based on certain grounds set out by the Law and the Courts interpretation thereto. There is little researches on the subject following the enactment, but was not supported and enriched with Court cases dealing with the new Law and its effect mainly on nullification and enforcement of the Arbitral Awards the issue that this study, which concentrate on all nullifications’ triggers during all the stages of the Arbitration process from signing the Arbitration agreement until obtaining the Arbitral Awards, aims to analyse it and how UAE Courts are dealing with nullification of Awards based on the New Law to help the Arbitration community understand and avoid any trivial or major mistakes that probably will lead to annulment of their Arbitral awards by analysing all possible triggers that may lead to the same and the methods to avoid them, all through excessive Court cases review and analysis for the past (4) years since the New Law came into force. As of date of writing this paper, the Courts have shown great appetite on avoidance of nullification of the Arbitral Awards and settled important principles on their interpretation and decisions worth considering, albeit with some unfavourable judgments to the Arbitration Community as it the case with any other litigation matters.